Citric acid cough threshold and airway responsiveness in asthmatic patients and smokers with chronic airflow obstruction. Issue 9 (September 1991) - Auffarth, B; de Monchy, J G; van der Mark, T W; Postma, D S; Koëter, G H
Abstract : The relation between citric acid cough threshold and airway hyperresponsiveness was investigated in 11 non-smoking patients with allergic asthma (mean FEV1 94% predicted) and 25 non-atopic smokers with chronic airflow obstruction (mean FEV1 65% predicted). Cough threshold was determined on two occasions by administering doubling concentrations of citric acid. Seven of the 11 asthmatic subjects and 14 of 25 smokers with chronic airflow obstruction had a positive cough threshold on both test days. Cough threshold measurements were reproducible in both groups (standard deviation of duplicate measurements 1.2 doubling concentrations in asthma, 1.1 doubling concentrations in chronic airflow obstruction). Citric acid provocation did not cause bronchial obstruction in most patients, though four patients had a fall in FEV1 of more than 20% for a short time on one occasion only. No significant difference in cough threshold was found between the two patient groups despite differences in baseline FEV1 values. There was no significant correlation between cough threshold and the provocative concentration of histamine causing a 20% fall in FEV1 (PC20) histamine in either group. Thus sensory nerves can be activated with a tussive agent in patients with asthma and chronic airflow obstruction without causing bronchial smooth muscle contraction.